Cornulitid tubeworms and other calcareous tubicolous organisms from the Hirmuse Formation (Katian, Upper Ordovician) of northern Estonia. (January 2023) - Vinn, Olev; Madison, Anna; Wilson, Mark A.; Toom, Ursula
Abstract: Seven species of cornulitids, one unidentified tubicolous shell, and the problematic bryozoan Lagenosypho Spandel, 1898 are here described from the Katian of Baltica. Three new species— Cornulites lindae new species, Cornulites meidlai new species, and Conchicolites kroegeri new species—are described. The unidentified tubicolous organism has punctate shell structure and setae-like structures that can best be affiliated with lophophorates. The Hirmuse fauna indicates that the diversity and number of cornulitids in the Ordovician of Baltica has been underestimated and it is likely that the Baltic cornulitid fauna was as diverse and abundant as the fauna of Laurentia. Clay mud-bottom environments supported the highest cornulitid diversity in the Late Ordovician of Baltica. The occurrence of intermediate forms indicates that some tentaculitid characters, e.g., regular annulation and a nearly straight shell, which were thought to be apomorphies of free-living tentaculitids, were actually inherited from ancestral cornulitids. The cornulitid fauna of the Late Ordovician of Laurentia somewhat resembles the cornulitid fauna of the Late Ordovician of Baltica, but there are fewer common faunal elements between Gondwana and Baltica. UUID: http://zoobank.org/cc704237-b578-4d06-a8ed-8457ca3ce972